A Tribe Called Red’s Halluci Nation: Sonifying Embodied Global Allegiances, Decolonization, And Indigenous Activism - Woloshyn, Alexa (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
“We are the tribe that they cannot see. We live on an industrial reservation. We are the Halluci Nation.” These words from Indigenous activist and poet John Trudell (1946–2015) inspired the latest album by Ottawa-based Indigenous DJ collective A Tribe Called Red (ATCR) and frame its pan-Indigenous, transcultural message. Inter-tribal relationships are both common and important to Indigenous communities, especially in urban centres. Powwows are also events that emphasize intertribal and intercultural relationships, even as they hosted by a specific nation. With Halluci Nation, ATCR seeks to foster far-reaching allegiances across culture, ethnicity, and place to “[understand] oppression and how to collectively dismantle oppression” (DJ NDN of ATCR).This article argues that ATCR’s Halluci Nation sonifies a process of decolonization that establishes an embodied network of global allies. I trace the development of ATCR’s music from its original focus on the Ottawa Indigenous community and its non-Indigenous allies to a call for nation-to-nation relationships (see Juno Award–winning album Nation II Nation, 2013), and then now to a concept album that seeks to manifest a real “Halluci Nation” with members from around the world. Analysis of ATCR’s music, audience, and Halluci Nation album is contextualized by studies of community formation and identity politics in intertribal initiatives), such as powwows and friendship centres, and pan-Indigenous activism, such as Idle No More.